Pengaruh Model Pembelajaran Inkuiri Terbimbing dengan Bantuan Scaffolding Kognitif Terhadap Keterampilan Menulis Ilmiah dan Hasil Belajar Siswa SMP - Supeno; Arista Eka kumalasari (PendIPA Journal of Science Education, 2026)
The current state of junior high school students' scientific writing skills and learning outcomes is still low due to the dominance of teacher-oriented learning models. This study aims to examine the effect of a guided inquiry learning model with cognitive scaffolding on junior high school students' scientific writing skills and learning outcomes in science learning. The approach used was quantitative with a quasi-experimental method and a non-equivalent posttest-only control group design. Purposive sampling was used to select samples, including two classes: the experimental class and the control class. Data analysis was carried out through three test phases: normality testing, homogeneity testing, and hypothesis testing. The data showed that the experimental class obtained a higher average score than the control class. This is evidenced by a significance value of 0.000, which is smaller than the 0.05 threshold, indicating that the implementation of a guided inquiry learning model with cognitive scaffolding has a significant effect on students' scientific writing skills and learning outcomes.